化简:n-mn-3(-mn-n)-(-m)-11
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 22:36:56
化简:n-mn-3(-mn-n)-(-m)-11化简:n-mn-3(-mn-n)-(-m)-11化简:n-mn-3(-mn-n)-(-m)-11
化简:n-mn-3(-mn-n)-(-m)-11
化简:n-mn-3(-mn-n)-(-m)-11
化简:n-mn-3(-mn-n)-(-m)-11
化简:n-mn-3(-mn-n)-(-m)-11
化简m/m-n-n/m+n+mn/m^-n^
2mn[(2mn)^2-3n(mn+m^2*n)-mn^2]计算
2mn[(2mn)²-3n(mn+m²n)-mn²
化简 m-2mn-n分之2m-3mn-2n
(5mn-2m+3n)+(-7m-7mn)
(5mn-2m+3n)+(-7m-7mn)
nbnnbnm,m,.mn,n,nm,mn,n,mn
急2[mn+(-3m)]-3(2n-mn),m+n=2 mn=-3
3(m^2n+mn)-4(mn-2m^2n)+mn.要有过程
已知m+n=3,mn=2/3,求mn-mn+mn的值
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
因式分解 mn(n-m)-n(m-n)
已知MN^2=-6,求-MN(M^2N^5-MN^3-N)的值
(m^2-n^2/mn)^2÷(m+n)^2*(m/m-n)^3 化简
m-n=7 mn=-5求(3m+5n+4mn)-(2n-4n+6mn)
已知:m<-n,mn>0,化简:|m|—|n|+|m+n|—|mn|.